Imagining climate resilient futures: A layered Delphi panel approach. (March 2023) - Flood, Stephen; Rogan, Fionn; Revez, Alexandra; McGookin, Connor; O'Dwyer, Barry; Harris, Clodagh; Dunphy, Niall; Byrne, Edmond; Gallachóir, Brian Ó; Bolger, Paul; Boyle, Evan; Glynn, James; et al.
Abstract: This paper in using a novel application of the Delphi panel method, explores and consolidates the future visions of a low carbon and climate resilient future in Ireland through community-based visioning processes that emerged through co-created, deliberative approaches at local level. It embraces a visioning process that applies a transdisciplinary approach, which aims to match different visions and stakeholder needs, combining bottom-up and top-down perspectives. Community visions were articulated by means of a series of deliberative futures workshops facilitated by the transdisciplinary project research team. Through iterations of the Delphi feedback loop, the notion of deep and shallow agreement is explored to examine the spectrum of consensus to dissent around the co-developed future visions and pathways of climate action, articulated by the Irish community case study. This approach enables a critical exploration of the conventional science-policy-practice nexus through the use of innovative creative communication and engagement methods. Findings suggest that more deliberative forums which bring together a diverse range of stakeholders are needed to develop a shared vision for the future; the importance of language use and the creation of a shared vocabulary of climate action; and the power of civic imaginaries in helping to create useful future narratives. Highlights: Novel Delphi panel application combining qualitative and quantitative methods. Embraces a visioning process that applies a transdisciplinary approach. Spectrum of consensus to dissent on co-developed future visions of climate action. Critical exploration of the conventional science-policy-practice nexus. More deliberative forums needed to develop a shared vision for the future.